2022
DOI: 10.1002/psp4.12834
|View full text |Cite
|
Sign up to set email alerts
|

A model‐based meta‐analysis of immune‐related adverse events during immune checkpoint inhibitors treatment for NSCLC

Abstract: Immune checkpoint inhibitors (ICIs) have become a vital part of the therapeutic landscape for non-small cell lung cancer (NSCLC) in recent years benefiting from their remarkable efficacy. However, ICIs are associated with potentially lifethreatening immune-related adverse events (irAEs). This study aims to quantify dose dependence and additional influencing factors of both any grade and grade greater than or equal to 3 irAEs in patients with NSCLC treated by ICIs. The triallevel irAE data was collected and poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…MBMA has been adopted in pharmaceutical research for a variety of disease areas, particularly in nervous system diseases, endocrine/nutritional/metabolic diseases, and neoplasms. For such types of diseases, multiple treatment strategies were developed and tested in many trials, allowing MBMA to estimate the relative effects of different treatments 9,20–24 . For most chronic diseases, such as diabetes and hypertension, which require long‐term management strategies, MBMA is particularly useful in predicting long‐term results based on short‐term data through time event or effect model 25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MBMA has been adopted in pharmaceutical research for a variety of disease areas, particularly in nervous system diseases, endocrine/nutritional/metabolic diseases, and neoplasms. For such types of diseases, multiple treatment strategies were developed and tested in many trials, allowing MBMA to estimate the relative effects of different treatments 9,20–24 . For most chronic diseases, such as diabetes and hypertension, which require long‐term management strategies, MBMA is particularly useful in predicting long‐term results based on short‐term data through time event or effect model 25 …”
Section: Discussionmentioning
confidence: 99%
“…For such types of diseases, multiple treatment strategies were developed and tested in many trials, allowing MBMA to estimate the relative effects of different treatments. 9,[20][21][22][23][24] For most chronic diseases, such as diabetes and hypertension, which require long-term management strategies, MBMA is particularly useful in predicting long-term results based on short-term data through time event or effect model. 25 Although MBMA has been increasingly used over time, our study suggested that the methodological and reporting quality of MBMA studies remained suboptimal.…”
Section: Articlementioning
confidence: 99%